Kluczowe elementy kapitału intelektualnego przedsiębiorstw - wyniki badań - Stańczyk-Hugiet, Ewa (Essential Elements of Intellectual Capital of Enterprises - Research Results, 2005)
The paper shows survey's results which concentrate on the importance of Intellectual Capital characteristics in enterprises. The research is concentrated on six characteristics: knowledge, organizational culture, reputation, brands, relations and intellectual rights. As a results it is identified that reputation, knowledge and brands are the most important characteristics of intellectual capital.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 399-407